2010
DOI: 10.1371/journal.pone.0011536
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of Mouse Embryonic Stem Cell-Derived Cardiac Progenitor Cells Preserves Function of Infarcted Murine Hearts

Abstract: Stem cell transplantation holds great promise for the treatment of myocardial infarction injury. We recently described the embryonic stem cell-derived cardiac progenitor cells (CPCs) capable of differentiating into cardiomyocytes, vascular endothelium, and smooth muscle. In this study, we hypothesized that transplanted CPCs will preserve function of the infarcted heart by participating in both muscle replacement and neovascularization. Differentiated CPCs formed functional electromechanical junctions with card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 51 publications
3
48
0
Order By: Relevance
“…Indeed, cell fusion experiments further demonstrated PACP ability to differentiate in vitro and to give rise to fusion events, reflecting a distinct property common to many types of cardiac progenitors, although this property appeared to be limited to aortaand ventricle-derived cells ( Figure 37). In particular, PACPs showed 5% rate of fusion events, consistent with previous data obtained using different cell types, such as mouse embryonic stem cells, human MSCs and human cardiac stem cells, that reported similar fusion efficiency (Pittenger et al 2004;Christoforou et al 2010;Acquistapace et al 2005). On the other hand, much higher fusion rate has been previously described for human and mouse mesoangioblasts (Galvez et al 2009;Galvez et al 2008;Galli et al 2005).…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, cell fusion experiments further demonstrated PACP ability to differentiate in vitro and to give rise to fusion events, reflecting a distinct property common to many types of cardiac progenitors, although this property appeared to be limited to aortaand ventricle-derived cells ( Figure 37). In particular, PACPs showed 5% rate of fusion events, consistent with previous data obtained using different cell types, such as mouse embryonic stem cells, human MSCs and human cardiac stem cells, that reported similar fusion efficiency (Pittenger et al 2004;Christoforou et al 2010;Acquistapace et al 2005). On the other hand, much higher fusion rate has been previously described for human and mouse mesoangioblasts (Galvez et al 2009;Galvez et al 2008;Galli et al 2005).…”
Section: Discussionsupporting
confidence: 90%
“…When engrafted into infarcted heart, ESC-derived CPCs differentiated into adult-sized CMs with Cx43 expression, reconstitute *20% of the scar tissue in a nonhuman primate model (12). Consistently, unlike PSC-derived CMs, PSC-derived CPCs appear to differentiate into mature CMs and vascular cells in the adult mouse heart without causing teratomas or arrhythmias (24,98). While these studies revealed the unique potential of CPCs to form adult-like CMs for heart regeneration, further investigation will be required to determine their morphological and functional maturation, coupling, and functional integration with host myocardium, and long-term survival and effects on heart function.…”
Section: Cardiac Progenitor Cellsmentioning
confidence: 87%
“…Monkey ES cell-derived cardiomyocyte precursors differentiated into cardiomyocytes, and replaced 1/5 of a cardiac scar in primates 8 . MESC derived cardiomyocytes transplanted in rodent hearts (Adler et al, 2010;Christoforou et al, 2010;Lu et al, 2010b), and sheep hearts , also contributed to cardiac repair.…”
Section: -Embryonic Stem Cellsmentioning
confidence: 99%
“…They justify the approaches taken in my studies to contribute to these areas of research. Although significant achievements have been reported from transplanting ES-derived cardiomyocytes onto animal hearts (Adler et al, 2010;Christoforou et al, 2010;Lu et al, 2010a;Stevens et al, 2009a;van Laake et al, 2009), the lack of a fully characterized cardiomyocyte purification protocol that can ensure a defined population of donor cells, 100% free of cells capable of forming tumours, has stalled progression of applying these findings to humans. In these studies, the use of DHP-R as a cardiomyocyte enrichment strategy may prove to be a valuable tool to purify ES-derived cardiomyocytes.…”
Section: -Conclusionmentioning
confidence: 99%